Gut Dysbiosis Associated with Antibiotics and Disease Severity and Its Relation to Mortality in Critically Ill Patients - Ojima, Masahiro (Dig Dis Sci, 2021)
BACKGROUND: The gut microbiota are reported to be altered in critical illness. The pattern and impact of dysbiosis on prognosis has not been thoroughly investigated in the ICU setting. AIMS: We aimed to evaluate changes in the gut microbiota of ICU patients via 16S rRNA gene deep sequencing, assess the association of the changes with antibiotics use or disease severity, and explore the association of gut microbiota changes with ICU patient prognosis. METHODS: Seventy-one mechanically ventilated patients were included. Fecal samples were collected serially on days 1–2, 3–4, 5–7, 8–14, and thereafter when suitable. Microorganisms of the fecal samples were profiled by 16S rRNA gene deep sequencing. RESULTS: Proportions of the five major phyla in the feces were diverse in each patient at admission. Those of Bacteroidetes and Firmicutes especially converged and stabilized within the first week from admission with a reduction in α-diversity (p < 0.001). Significant differences occurred in the proportional change of Actinobacteria between the carbapenem and non-carbapenem groups (p = 0.030) and that of Actinobacteria according to initial SOFA score and changes in the SOFA score (p < 0.001). An imbalance in the ratio of Bacteroidetes to Firmicutes within seven days from admission was associated with higher mortality when the ratio was > 8 or < 1/8 (odds ratio: 5.54, 95% CI: 1.39–22.18, p = 0.015). CONCLUSIONS: Broad-spectrum antibiotics and disease severity may be associated with gut dysbiosis in the ICU. A progression of dysbiosis occurring in the gut of ICU patients might be associated with mortality. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s10620-021-07000-7.